THE USE OF FLASH GAME IN IMPROVING STUDENTS’ VOCABULARY (A Classroom Action Research on the Third Grade Students of Extracurricular English Class of SD Islam Al-Azhar 21 Pontianak in Academic Year 2013/2014) - Sucitawati, Windi; ., Sofian; Rosnija, Eni (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2014)
This research was held to improve students’ vocabulary by teaching using flash games. It was a Classroom Action Research which is conducted in two cycles. The subject of this research was the Third Grade Studentsof Extracurricular English Class of SD Islam Al-Azhar 21 Pontianak in Academic Year 2013/2014. The data was collected by using observation checklist, fieldnotes and written test. The data was analyzed by describing the observation checklist and fieldnotes. It also used mean score to score the test and percentage to score the observation checklist. The results indicate the students’ vocabulary improved by teaching using flash games.The mean score in the first cycle was 66.5 and in the second cycle was 93.5. The average score on meaning aspect in the first cycle was 57.50 and 97.50 in the second cycle. The average score on spelling aspect in the first cycle was 63.33 and 86.66 in the second cycle. The average score on usage aspect in the first cycle was 73.33and 95.00 in the second cycle. Key words: Vocabulary, Flash games   Abstrak: Penelitian ini dilaksanakan untuk meningkatkan kosa kata siswa dengan mengajar menggunakan permainan flash. Penelitian ini adalah Penelitian Tindakan Kelas yang dilaksanakan dalam dua siklus. Subjek dalam penelitian ini adalah siswa kelas tiga SD kelas ekstrakurikuler Bahasa Inggris di sekolah Islam Al-Azhar 21 Pontianak tahun ajaran 2013/2014. Data penelitian dikumpulkan melalui ceklis observasi, catatan lapangan dan tes tertulis. Data tersebut  dianalisa dengan mendeskripsikan ceklis observasi dan catatan lapangan. Analisa data juga dilakukan dengan cara mencari nilai rata-rata dalam menilai tes dan persentase dalam menilai ceklis observasi. Hasil penelitian menunjukkan kosa kata siswa meningkat dengan mengajar menggunakan permainan flash. Nilai rata-rata siswa di siklus pertama adalah 66.5 dan pada siklus kedua adalah 93.5. Nilai rata-rata pada siklus pertama dalam aspek arti adalah 57.50 dan 97.50 pada siklus kedua. Nilai rata-rata pada siklus pertama dalam aspek ejaan adalah 63.33 dan 86.66 pada siklus kedua. Nilai rata-rata pada siklus pertama dalam aspek penggunaan adalah 73.33 dan 95.00 pada siklus kedua. Kata kunci: Kosa kata, permainan flash